Replicon-seq: seeing is believing. Issue 10 (October 2022) - Polo Rivera, Cristian; Deegan, Tom D.
Abstract : Claussin et al. introduce Replicon-seq, a new genome-wide DNA sequencing technology that monitors the progression of individual replisomes at high resolution in vivo.